Pengaruh Pembentukan Alur Trapesium Pada Pelat Galvanil dengan Proses Bead Roller Terhadap Frekuensi Alami Pada Kondisi Batas Jepit – Jepit - Harsono, Abimanyu; Adipura, Anandri Indra; Erwanto, Erwanto (Politeknik Negeri Padang, 2024)
Galvanized steel sheet is a low carbon steel that is often used in the manufacturing industry, especially in the automotive industry, this is because galvanized sheet has properties that are ductile, easy to form and resistant to corrosion, making it suitable for application as a vehicle body, but low carbon steel sheet has limitations on the level of stiffness of the sheet so that it will affect comfort due to vibration when applied to vehicle construction. The stiffness of the sheet can be increased by forming a groove profile through the rolling process and increasing the thickness of the sheet so that its stiffness and natural frequency value will increase. The purpose of this study is to determine the effect of trapezoidal groove formation on the natural frequency of galvanized sheet by the rolling process using a bead rolling die with variations in groove width, groove depth and sheet thickness. The research method used is the experimental method, starting with the determination of the plate dimensions, the determination of the groove width and depth, the process of making groove profiles, the measurement and analysis of the results of the natural frequency values and plate stiffness. The dimensions of the test plates were 575 mm x 600 mm with thicknesses of 0.6 mm and 0.8 mm. The results showed that the increase in natural frequency and stiffness was affected by residual stress and plate thickness. The highest frequency obtained was 330.60 Hz on a plate with a groove width of 12 mm and a groove depth of 5 mm with a thickness of 0.8 mm, this result has increased compared to a smooth plate which is only 30.76 Hz.